Application of Response Surface Methodology for Optimizing Tensile Strength of Rice Husk Fiber-Reinforced Polylactic Acid Composites - Yiga, Vianney Andrew; Lubwama, Michael; Olupot, Peter Wilberforce (MDPI, 2021)
Filler/fiber loading and surface modification significantly influence tensile properties of natural fiber-reinforced plastic composites. It is therefore pertinent that they are suitably selected in order to yield the optimum tensile properties. Fiber-reinforced PLA composites were prepared us-ing compression molding with Box-Behnken Design experimental design approach. Factors, namely clay filler loading (1−5 wt.%), rice husk fiber loading (10−30 wt.%), alkali concentration (0−4 wt.%), rice husk variety (K85, K98) and alkali type (NaOH, Mg(OH)2) were varied. ANOVA determined significance of the factors affecting composites’ tensile strength. ANOVA results revealed the re-duced cubic model as best fit for tensile strength response. The desirability function revealed that variable values leading to optimum tensile strength (33.67 MPa) were 4.97 wt.%, 11.16 wt.% and 3.99 wt.% for filler loading, fiber loading and alkali concentration, respectively.
Keywords: Clay; Optimization; Polylactic acid; PLA composites; Rice husks; RSM; Tensile strength